Blue Rubber Bleb Nevus Syndrome (BRBNS): A Rare Cause of Refractory Anemia in Children - Liang-Chun Chen; Chun-Yan Yeung; Chen-Wang Chang; Hung-Chang Lee; Wai-Tao Chan; Chuen-Bin Jiang; Szu-Wen Chang (MDPI AG, 2022)
Refractory anemia is not uncommon in pediatric patients, and anemia caused by gastrointestinal tract bleeding should always be kept in mind. Aside from infection or intestinal malrotation related bleeding, vascular malformation should also be considered. Blue rubber bleb nevus syndrome (BRBNS) is a rare vascular disorder consisting of multiple venous malformations. Lack of experience in pediatric BRBNS might lead to delayed diagnosis or misdiagnosis. Herein, we report a case of an eleven-year-old boy with recurrent pallor appearance and weakness diagnosed with BRBNS. After a thorough examination, he was treated with endoscopic polypectomy, and further iron supplements and folic acid. He is now under regular follow-up at our outpatient department. No complication is noted for six months. BRBNS is a rare venous malformation syndrome that mostly involves skin and the gastrointestinal tract. Multidisciplinary approach should be arranged for diagnosis and management. Up to date, no consensus for BRBNS treatment has been reached. Management usually depends on clinical symptoms and severity of damage of involved organs. The options of treatment include conservative, medical, endoscopic, and surgical management.